Impacts of Amenorrhea on Fertility and Pregnancy Outcomes in Females with Anorexia Nervosa - Dr. Aidah Alkaissi (My University, 2010)
Purpose:
To examine the effects of amenorrhea on fertility and pregnancy outcome in women with anorexia nervosa
Methods:
The method used was a model for literature-based theses of Friberg et al (2006). In search of the literature database PubMed was used. Articles were reviewed following the models of Polit et al (2006) and Willman et al (2006) and quality was assessed according to criteria from the SBU (1999). Inclusion and exclusion criteria were formulated. The analysis was conducted in three stages, the selected studies, read the (first stage), similarities and differences were examined (second step), and the results then interpreted and grouped into five different themes (third step).
Results/findings:
The following five themes were identified: (1) Features of anorexia nervosa (AN) is the refusal to maintain body weight for age and height, fear of gaining weight, self-evaluation, press on the weight, shape and appearance (Zerbe 2006). AN is accompanied with multiple endocrine abnormalities. Hypothalamic monoamines (especially serotonin), neuropeptides (especially neuropeptide Y and Cholecystokinin) and leptin are involved in the regulation of human appetite, and in many ways they are changed in AN. AN appears to be a reflection of the female ability to alter maturation rates and reproductive function in response to environmental conditions (Surbey 1987). (2) Amenorrhea: is one of the diagnostic criteria of AN (Rollins et al 1978). It occurs when there is a shortage of calories due to inadequate nutrient intake for the amount of consumed energy
(Laughlin et al 1998). Increased secretion of adrenocorticotropic hormone and proopiomelanocortin seems to be secondary to starvation. Hypothalamic amenorrhea, not only related to the low body weight and exercise. Growth hormone resistance with low production of insulin-like growth factor I and high growth hormone reflects nutritional loss. (Støving 1999). Patients with moderate to severe AN often has a hypoestrogenic amenorrhea, which exposes these patients to osteoporosis and pathological fractures (Yager 2000). Approximately 85% of patients will have spontaneous return of menstruation within six months after reaching a weight of 90% of ideal body weight (Golden 1997) (3) Hormone replacement therapy (HRT): Since AN is accompanied by amenorrhea, HRT used to improve the patient's bone density and begin menstruation. The evidence supports the use of HRT in patients with AN is feeble. Because estrogen induces monthly menstrual bleeding, the anarotic patient may believe that her body works well when it is not. There is a clinical consensus recommends that menstruation does not occur artificially in anorectic patients (Grin Spoon 2002), nutritional stabilization, to prevent bone loss remain the cornerstone of treatment. (4) Spontaneous weight gain: is accompanied by a significant increase in trunk adiposity and estrogen use may not protect against the accumulation of central fat with weight gain (Grin Spoon et al 2001). Several studies have failed to show any positive correlation between the HRT and bone mineral density (Hay 1999, Golden et al 2002). (5) Pregnancy outcome: In severe malnutrition, ovaries seem small, and have no follicles (de Zwaan 1997). The physical appearance of a woman can reveal muscle wasting, minimal breast tissue, and vaginal atrophy. A few of the women cease to menstruate and are not fertile during difficult periods (Bulik 1999). A history of infertility can be an indicator of previous eating disorders. In a study among women who were introduced to treat infertility, showed that as many as 17% had a diagnosed eating disorder (Stewart 1987). Actively ill women and women with a history of AN have a higher rate of miscarriage than healthy women (Gieleghem 2002). A higher rate of caesarean section (Franko et al 2000), a 40% in the number of low birth weight babies and increased incidence of premature delivery (Conti 1998) were reported. Furhermore, Bulik et al (1999) reported no differences between women with a history of AN and controls on rate of pregnancy, mean number of pregnancies per female, or age at first pregnancy.
Conclusions:
Amenorrhoea is a common cause to encourage women to apply for gynecological evaluation. Medical providers should help patients and their families to have access to multidisciplinary care with a mental health provider, dietician, dentist and experienced medical provider. Primary care physicians have a crusial role to note the severity of this chronic mental illnesses while assessing the patient's physical status. Future research aimed at prevention of AN by early identification and education leading to a better understanding of this life-threatening illness

Purpose:
To examine the effects of amenorrhea on fertility and pregnancy outcome in women with anorexia nervosa
Methods:
The method used was a model for literature-based theses of Friberg et al (2006). In search of the literature database PubMed was used. Articles were reviewed following the models of Polit et al (2006) and Willman et al (2006) and quality was assessed according to criteria from the SBU (1999). Inclusion and exclusion criteria were formulated. The analysis was conducted in three stages, the selected studies, read the (first stage), similarities and differences were examined (second step), and the results then interpreted and grouped into five different themes (third step).
Results/findings:
The following five themes were identified: (1) Features of anorexia nervosa (AN) is the refusal to maintain body weight for age and height, fear of gaining weight, self-evaluation, press on the weight, shape and appearance (Zerbe 2006). AN is accompanied with multiple endocrine abnormalities. Hypothalamic monoamines (especially serotonin), neuropeptides (especially neuropeptide Y and Cholecystokinin) and leptin are involved in the regulation of human appetite, and in many ways they are changed in AN. AN appears to be a reflection of the female ability to alter maturation rates and reproductive function in response to environmental conditions (Surbey 1987). (2) Amenorrhea: is one of the diagnostic criteria of AN (Rollins et al 1978). It occurs when there is a shortage of calories due to inadequate nutrient intake for the amount of consumed energy
(Laughlin et al 1998). Increased secretion of adrenocorticotropic hormone and proopiomelanocortin seems to be secondary to starvation. Hypothalamic amenorrhea, not only related to the low body weight and exercise. Growth hormone resistance with low production of insulin-like growth factor I and high growth hormone reflects nutritional loss. (Støving 1999). Patients with moderate to severe AN often has a hypoestrogenic amenorrhea, which exposes these patients to osteoporosis and pathological fractures (Yager 2000). Approximately 85% of patients will have spontaneous return of menstruation within six months after reaching a weight of 90% of ideal body weight (Golden 1997) (3) Hormone replacement therapy (HRT): Since AN is accompanied by amenorrhea, HRT used to improve the patient's bone density and begin menstruation. The evidence supports the use of HRT in patients with AN is feeble. Because estrogen induces monthly menstrual bleeding, the anarotic patient may believe that her body works well when it is not. There is a clinical consensus recommends that menstruation does not occur artificially in anorectic patients (Grin Spoon 2002), nutritional stabilization, to prevent bone loss remain the cornerstone of treatment. (4) Spontaneous weight gain: is accompanied by a significant increase in trunk adiposity and estrogen use may not protect against the accumulation of central fat with weight gain (Grin Spoon et al 2001). Several studies have failed to show any positive correlation between the HRT and bone mineral density (Hay 1999, Golden et al 2002). (5) Pregnancy outcome: In severe malnutrition, ovaries seem small, and have no follicles (de Zwaan 1997). The physical appearance of a woman can reveal muscle wasting, minimal breast tissue, and vaginal atrophy. A few of the women cease to menstruate and are not fertile during difficult periods (Bulik 1999). A history of infertility can be an indicator of previous eating disorders. In a study among women who were introduced to treat infertility, showed that as many as 17% had a diagnosed eating disorder (Stewart 1987). Actively ill women and women with a history of AN have a higher rate of miscarriage than healthy women (Gieleghem 2002). A higher rate of caesarean section (Franko et al 2000), a 40% in the number of low birth weight babies and increased incidence of premature delivery (Conti 1998) were reported. Furhermore, Bulik et al (1999) reported no differences between women with a history of AN and controls on rate of pregnancy, mean number of pregnancies per female, or age at first pregnancy.
Conclusions:
Amenorrhoea is a common cause to encourage women to apply for gynecological evaluation. Medical providers should help patients and their families to have access to multidisciplinary care with a mental health provider, dietician, dentist and experienced medical provider. Primary care physicians have a crusial role to note the severity of this chronic mental illnesses while assessing the patient's physical status. Future research aimed at prevention of AN by early identification and education leading to a better understanding of this life-threatening illness
Impacts of Amenorrhea on Fertility and Pregnancy Outcomes in Females with Anorexia Nervosa